Retroperitoneal Giant Schwannoma: Difficulties in Diagnosis and Subsequent Surgical Management (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Management and excision of left hypochondriac mass of a  55 year old lady have been presented in the paper. The  ultrasound of whole abdomen showed two big lumps in the  left hypochondriac and lumbar region which after excision  turned out to be a retroperitoneal schwannoma. The mass  was removed by sacrificing the left kidney. Though it is a  highly specialized operation and should be performed in a  specialized center, sometimes general surgeons are unable  to avoid the operation due to low economic condition of the  patient. The case was performed at the Central Medical  College Hospital, Comilla utilizing the existing facilities.  Fortunately the patient is doing well and leading a normal  life after one and half years of operation   DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11420   J Bangladesh Coll Phys Surg 2012; 30: 105-107